Taxonomic study of crustose coralline algae off the northeastern Brazilian coast - Costa, Iara Oliveira; Horta, Paulo Antunes; Bergstrom, Ellie R; Nunes, José Marcos De Castro (Phytotaxa, 2014)
This work presents a detailed morphoanatomical study of crustose coralline algae species from the northeastern Brazilian coast, in the north of Bahia state. Nine species have been recognized: Sporolithon episporum, Lithophyllum stictaeforme, Spongites yendoi, Spongites sp., Mesophyllum erubescens, Phymatolithon masonianum, Phymatolithon calcareum, Lithothamnion crispatum and Lithothamnion brasiliense. Phymatolithon masonianum and Phymatolithon calcareum constitute the first record of these species for the northern coast of Brazil. An identification key, as well as descriptions, illustrations, comparisons with related taxa, and geographical distributions for Brazil as well as global geographic distributions are presented. Additionally, some ecological implications are discussed focusing the need of more studies about this neglected group of coralline red algae.